Trithuria brevistyla (Hydatellaceae), a new combination for the New Zealand endemic species from the South Island - de Lange, P.J.; Mosyakin, S.L. (Український ботанічний журнал, 2019)
A new combination, Trithuria brevistyla (K.A.Ford) de Lange & Mosyakin, is proposed for the recently described New Zealand, South Island endemic taxon originally published as T. inconspicua subsp. brevistyla K.A.Ford. Species rank for that taxon is advocated on the basis of morphological and reproductive distinctions between that species and the closely related North Island, New Zealand endemic T. inconspicua Cheeseman sensu stricto. Some general considerations on optional species versus subspecies ranks for plant taxa in need of conservation are provided. Нова комбінація Trithuria brevistyla (K.A.Ford) de Lange & Mosyakin запропонована для щойно описаного з Південного острова Нової Зеландії ендемічного таксона, що був опублікований як T. inconspicua subsp. brevistyla K.A.Ford. Видовий ранг для цього таксона обґрунтований на основі його морфологічних та репродуктивних відмінностей від близько спорідненого виду T. inconspicua Cheeseman sensu stricto, який є ендеміком Північного острова Нової Зеландії. Обговорені деякі загальні міркування щодо можливості визнання видового або підвидового рангу таксонів рослин, що потребують охорони.